Research on the “professional, ideological, and innovative” tri-integration reform of the “computer network security” course in the context of artificial intelligence - Liu Li (ITM Web of Conferences)
With the rapid development of information technology, artificial intelligence has become a significant force driving social transformation. In this context, the "Computer Network Security" course faces unprecedented challenges and opportunities. This paper explores how to integrate professional knowledge teaching, ideological education, and innovation and entrepreneurship training (referred to as "Professional, Ideological, and Innovative" or "PII") into the "Computer Network Security" course in the context of artificial intelligence, aiming to enhance students' comprehensive qualities and innovative capabilities. By reforming teaching content, methods, and evaluation systems, this paper seeks to construct a curriculum system that meets the demands of the new era, providing strong support for cultivating compound talents with cybersecurity awareness and innovation capabilities.